Insulin resistance (IR) in women with polycystic ovary syndrome (PCOS): are their female relatives at risk of metabolic disease ? - Egodage, C.S.; Goonewardena, A.U.A.; Pathmakumara, A.; Balen, A.H.; Wijeyaratne, C.N. (My University, 2002)
OBJECTIVE: To compare insulin resistance and fasting plasma lipids of women with and without PCOS and to assess prevalence of metabolic disease, IR and lipid concentrations in the first degree female relatives of women with PCOS, METHOD: Consecutive consenting women with anovular PCOS (with ultrasound evidence of polycystic ovaries and clinical features), their consenting first-degree female relatives (mothers and sisters) and unrelated normal women of reproductive age were recruited. BMI, waist to hip ratio (WHR) were recorded and fasting blood glucose (FBG), insulin and plasma lipids were measured in all subjects. IR was estimated by a mathematically validated QUICKI analysis of insulin sensitivity. RESULTS: 77 women with PCOS, 37 mothers 10 sisters of women with PCOS and 45 controls were recruited. PCOS VS. CONTROLS: The average age of women with PCOS was 27.2 +/- 0.7, and of controls 33.1 +/- 0.8 (p = 0.28). PCOS vs. controls had a BMI of 26.3 +/- 0.95 vs. 23 +/- 0.1 (p = 0.3) and WHR of 0.95 +/- 0.03 vs. 0.79 +/- 0.02 (p = 0.03). PCOS vs controls had FBG of 5.41 +/- 0.18 vs. 4.95 +/- 0.21 mmol/l (NS); fasting insulin of 246 +/- 67 vs. 75.7 +/-14 pmol/1 (p = <0.001); QUICKI 0.305 +/- 0.22 vs 0.333 +/- 0.24 (p = 0.0006); fasting cholesterol 232 +/- 12 vs. 221 +/- 11.8 mmol/1 (p = 0.14), triglycerides 124 +/-8.9 vs. 101 +/- 10.8 mmol/1 (p = 0.03) and HDL 44 +/ - 4.8 vs. 51.2 +/- 7.9 mmol/1 (p= 0.01). RELATIVES OF PCOS SUBJECTS: The mothers were aged 52 +/- 4 years of whom 13 (35 percent) had type 2 diabetes mellitus, 9 (24 percent) were hypertensive and 3 (0.08 percent) had dyslipidaemia. The average age of sisters was 28.2 +/-1 with and 4 were diagnosed to have PCOS. The mean value of QUICKI was 0.324 (PCOS vs. relatives p = 0.01); fasting cholesterol 260 (PCOS vs. relatives p = 0.02); triglycerides 159 +/- 18 (p = 0.05) and HDL 50.9 +/- 4.7 mmol/l (p = 0.11). CONCLUSION: Subjects with PCOS have-greater central obesity, greater insulin resistance, higher triglycerides and lower HDL than age and BMI matched controls; and have significantly greater IR than their female relatives. Mothers of subjects with PCOS have a high prevalence of type 2 diabetes and hypertension while sisters have a 40 percent prevalence of PCOS.
Keywords: PCOS; INSULIN RESISTENCE